My ah ma make one - Lin, Yanxiang (2015)
My Ah Ma Make One is a social movement to celebrate Singapore’s unique snacks heritage against the backdrop of the nation’s fiftieth birthday (SG50). Launched by four final year students from Nanyang Technological University, Wee Kim Wee School of Communication and Information, the campaign aimed to preserve and promote traditional snacks among youth today. This campaign primarily targeted youth aged between 18 to 35 years old, who would be the heirs of the local traditional snack heritage. Leveraging on narrative persuasion through the sharing of stories and skills, the team sought to also foster intergenerational bonds among grandparents and grandchildren as an auxiliary effort. Through the integrated use of social media and island-wide physical events, the campaign effectively raised the level of knowledge of local traditional snack heritage among youth, and increased their behavioral intents to learn about traditional snacks and bond with grandparents during the process. Beyond the requisites, the team also worked with sponsors and partners to prolong the campaign’s lifespan through a scheduled publication. This report showcases the primary and secondary research conducted, which formed the bedrock of the campaign and gave birth to the creative plans executed. The assorted yet complementary strategies and tactics are discussed and evaluated for their effectiveness, based on the initial impact and output objectives crafted. Besides significant achievements, limitations of the campaign and recommendations to improve its overall impact and sustainability are also covered, in the hope of inspiring successors to continue the conservation efforts of the local traditional snack heritage. Original documents, collateral materials, as well as comprehensive tables and charts are included in the appendices for additional reference.